A multi-decadal and social-ecological systems analysis of community waterpoint payment behaviours in rural Kenya. (October 2016) - Foster, Tim; Hope, Rob
Abstract: Community-based financing of rural water supply operation and maintenance is a well-established policy principle in sub-Saharan Africa. Yet evidence from over 90, 000 waterpoints in five sub-Saharan African countries suggests a majority of communities fail to establish and sustain a revenue collection system. As a result, insufficient finances to repair waterpoints can lead to lengthy downtimes or abandonment, threatening the health and welfare of millions of water users forced to revert to unsafe or distant alternatives. Applying a social-ecological systems framework to community waterpoints in rural Kenya, we empirically assess the prevalence and determinants of financial contributions among water users. The analysis draws on multi-decadal data covering 229 years' worth of water committee financial records consisting of more than 53, 000 household payments. Results reveal that non-payment and late payment are prevalent, and payment behaviours are predicted by groundwater quality, waterpoint location, productive water use, and rainfall season. The findings reflect the socio-ecological nature of waterpoint sustainability in rural sub-Saharan Africa and confirm that households are not always willing and able to pay for an improved water supply. This situation is symptomatic of a fundamental operation and maintenance financing challenge that must be addressed if the Sustainable Development Goal of universal access to safe water is to be achieved. Graphical abstract: Highlights: We analyse more than 53, 000 payments by waterpoint users in rural Kenya. Results suggest non-payment and late payment are prevalent. Payment levels predicted by water quality, accessibility, productive uses and rainfall.